Children who Leave the Emergency Department: Missing Opportunities? - Machado, Virgínia (2014)
Introduction: Children who leave the Emergency Department may be at risk for preventable health problems related to the lack of timely assessment.Objective: The aim of this study was to evaluate and characterize the cases of children leaving our Emergency Department and to determine their clinical outcome.Material and Methods: A retrospective and descriptive review of the patient’s medical records was conducted. All children leaving the Emergency Department of Hospital de São Bernardo between January 1 and December 31, 2012, were included in the study.Results: A total of 538 children abandoned the Emergency Department (1.35 % of all admissions). The majority (89.5%) had no criteria for urgent assessment and abandoned before medical observation (82.7%). The percentage of leaving was higher in the months of December, January and February (64%), on Tuesday (19.3%) and in the afternoon shift (60.8%). These periods coincided with the peak inflow of patients to the Emergency Department. The waiting time for medical observation was in most cases (94.4%) appropriate to the clinical severity. Six patients returned within 72 hours, 2 requiring hospitalization.Discussion: The percentage of patients that walked-out from the Emergency Department was within the excepted range. A non-urgent triage level and prolonged waiting times were predisposing factors to abandonment.Conclusion: Overcrowding of the Emergency Department with children with non-urgent problems, that increase waiting times, can lead to abandonment with unfavorable outcome, which in our series occurred in only 2 cases.Keywords: Child; Patient Dropouts; Emergency Service, Hospital; Waiting Lists; Time Factors; Portugal.